ASSESSMENT OF RISKS TO THE HEALTH OF THE POPULATION OF AN INDUSTRIAL CITY ASSOCIATED WITH ATMOSPHERIC EMISSIONS FROM THE CONSTRUCTION INDUSTRY - Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна; Мотуз, Ирэна Юрьевна; Штайгер, Варвара Адамовна (Medicine in Kuzbass, 2022)
Subject of research – atmospheric emissions of the construction industry. Objective of research – assess the risk to public health from the effects of atmospheric emissions from Kuznetsk Light Construction Plant LLC, located in the city of Novokuznetsk, Kemerovo Region. Methods of research. The assessment of the emissions of the enterprise based on the analysis of the volume of maximum permissible emissions. The indices of hazard of pollutants were calculated. The maximum and average annual concentrations of pollutants at each point of exposure to concentrations associated with residential microdistricts were determined. The risks of chronic intoxication and carcinogenic risks to public health have been calculated. The resulting risk values were compared with the acceptable risk levels. Main results. Substances have been identified that have a major share in the total emissions of the enterprise. Among the non-carcinogenic substances, the main pollutants were suspended solids, as well as dimethylbenzene (xylene), iron trioxide, white spirit and kerosene. The main carcinogen in the plant’s emissions is hexavalent chromium. The indices of non-carcinogenic and carcinogenic hazard of pollutants were determined. The highest indices of non-carcinogenic hazard were found for manganese and its compounds, suspended solids and dimethylbenzene (xylene). Chromium has the highest carcinogenic hazard index. The risks of chronic intoxication and carcinogenic risks were calculated for the points of exposure to concentrations. Comparison of the total risks of chronic intoxication and carcinogenic risk with acceptable levels in the selected micro-districts of the city was carried out. Conclusions. The obtained risk values do not exceed the acceptable level, therefore, atmospheric emissions from the Kuznetsk lightweight construction plant do not have a significant impact on the health of the city residents.